Zinc oxide-based saturable absorber for generation of passively Q-switched and mode-locked erbium- doped fiber laser - Syed Husin, Syarifah Aloyah (2018)
There are two techniques that can be used to generate the mode-locked and Q-switched pulses namely active and passive technique. The passive technique is more preferable compared to the active technique due to its simplicity and easy operation. Passively pulsed fiber laser regimes can be generated by saturable absorber device. However, most of the SA used earlier have some limitation in terms of the optoelectronic properties, making them undesirable for certain optoelectronic applications. Zinc oxide (ZnO), a semiconductor of II-IV group, has a high potential as the saturable absorber (SA) which holds the advantage of easily available and inexpensive. In addition, the high third-nonlinear coefficient and ultrafast recovery time of ZnO also become its some plus points towards suitable and promising candidate as SAs, which could offer another alternative to the existing SA materials. This study introduces two techniques of fabrication of ZnO-based SA for the application in Q-switched and mode-locked fiber laser generation. The first technique is called as the evaporation technique whereby ethanol solution is used to adhere ZnO powder on the surface of a fiber ferrule through the evaporation process. The second technique is called as the ZnO-PDMS polymer composite-clad microfiber whereby the ZnO powder is mixed with the polydimethylsiloxane (PDMS) polymer to be coated around the microfiber. The structural properties of the fabricated ZnO-based SA by both techniques are characterized by Raman spectroscopy, field emission scanning electron microscopy (FESEM) and high power microscopy and their saturable absorption properties are characterized by dual measurement setup. The modulation depth and saturation intensity for the ZnO-based SA by evaporation technique are measured to be 1.7% and 0.0014 MWcm-2. On the other hand, the modulation depth and saturation intensity for the ZnO-PDMS polymer composite-clad microfiber are measured to be 6.4% and 4.15 MWcm-2 respectively. A Q-switched erbium-doped erbium-doped fiber laser (EDFL) is successfully demonstrated by inserting the ZnO-based SA deposited by the evaporation technique into the laser cavity. Self-started and stable Q-switching is achieved at a low power of 20.34 mW. At the maximum pump power of 48.58 mW, the Q-switched EDFL generates the central wavelength, pulse repetition rate, pulse width, average output power and pulse energy of 1558.32 nm, 25.93 kHz, 3.65 μs, 0.46 mW and 19.34 nJ respectively. On the other hand, the integration of the ZnO-PDMS polymer composite-clad microfiber into the laser cavity results in mode-locked pulse generation. The mode-locked laser has a central wavelength, 3 dB spectral bandwidth, pulse duration, pulse repetition rate and time-bandwidth product of 1558 nm, 5.02 nm, 1.03 ps, 9.77 MHz and 0.6266 respectively. These results indicate that the proposed ZnOPDMS polymer composite-clad microfiber could be useful as a simple, low-cost and ultrafast SA device.